Comparison of Dexamethasone Pharmacokinetics in Female Rats after Intravenous and Intramuscular Administration - Samtani, Mahesh N. (2005)
This study seeks a route of drug administration that would produce a pharmacokinetic profile for dexamethasone not significantly different from the intravenous route in female rats and would offer reproducible drug input with minimal stress to the animals. The intramuscular (IM) route of drug administration vs intravenous (IV) injection were compared in three female Wistar rats administered 1 mg/kg dexamethasone phosphate. Dexamethasone plasma concentrations were measured by a normal phase HPLC assay for 12 h after drug administration. Dexamethasone exhibited monoexponential behavior after intravenous dosing and was absorbed rapidly after intramuscular dosing (absorption half-life of 14 min) with 86% bioavailability. Dexamethasone had a terminal half-life of 2.3 h after drug administration by either route. The volume of distribution of 0.78 l/kg and the clearance of 0.23 l/h/kg are in good agreement with reported pharmacokinetic parameters in male rats. Intravenous dosing can be replaced by intramuscular dosing without causing any marked difference in dexamethasone pharmacokinetics.